Pengaruh Pretreatment Inokulum Terhadap Proses Aklimatisasi Degradasi Anaerob - Shella Zahrawani; David Andrio; Evelyn Evelyn (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Palm Oil Mill Effluent (POME) has total COD concentration 44.444 mg/L, with the high value of total COD it is very suitable to be processed anaerobically. To maximize the process of degradation of the substrate by bacteria can be done by the process of adapting bacteria or which can be called the acclimatization process. This acclimatization process uses two types of substrate, glucose and POME. The use of bovine rumen which is a mixed culture bacteria as an inoculum can benefit because of the diversity of microorganisms contained in it. This study was conducted in Circulating Bed Reactor (CBR) as semi batch reactor with working volume of 5L, ratio of substrate : inoculum = 70:30 %(v/v). This research aimed to study the effect of pretreatment inoculum in order to increase substrate degradation. This process was done in five days for every substrate with removal efficiency of soluble COD and growth rate of VSS in acclimatization phase I was 83,33% and 1.333 mg/L/day and in acclimatization phase II was 75% and 2,000 mg/L/day, respectively.Keyword: Palm oil mill effluent, Acclimatization process, Mixed culture bacteria, soluble COD, VSS